Association between dietary inflammatory index score and cardiovascular-kidney-metabolic syndrome: a cross-sectional study based on NHANES - Yu, Huang; Liu, Yankun; Zhang, Tingyi; Guan, Ziyi; Li, Ping (Frontiers in Nutrition, 2025)
BackgroundCardiovascular-kidney-metabolic (CKM) syndrome affects 25% of US adults, with chronic inflammation as a key pathophysiological mechanism. While the inflammatory basis of CKM syndrome is established, associations of the energy-adjusted dietary inflammatory index (E-DII) with CKM syndrome remain unexplored in the general population.MethodsUsing data from 7,110 participants in the National Health and Nutrition Examination Survey (2007–2018), we examined the association between E-DII (calculated from dietary recall data) and CKM syndrome (defined as co-occurrence of cardiometabolic syndrome and chronic kidney disease). Multiple logistic regression, restricted cubic spline analyses, weighted quantile sum regression, and quantile g-computation were performed to assess associations and dietary component contributions.ResultsHigher E-DII scores correlated with increased CKM syndrome prevalence (OR: 1.22, 95% CI: 1.09–1.37). The relationship exhibited linearity (p for nonlinearity = 0.464). Stratified analyses across demographic and socioeconomic subgroups revealed consistent associations. Component analyses identified alcohol as the dietary factor with the strongest association with CKM syndrome.ConclusionThe findings demonstrate a significant association between dietary inflammatory potential and CKM syndrome, with alcohol consumption emerging as a key modifiable factor. These results provide evidence-based insights for developing targeted dietary interventions in CKM syndrome prevention.